2013
DOI: 10.1111/ijn.12028
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism (VTE) risk assessment: Rural nurses' knowledge and use in a rural acute care hospital

Abstract: It is estimated that about 2000 people die as a result of venous thromboembolism (VTE) each year, with a further 30,000 being hospitalized. Prophylaxis significantly reduces VTE morbidity and mortality, and thus represents a real long-term health-care benefit. The aim of this study was twofold: (i) to assess the current level of compliance to VTE risk assessment and prophylaxis best practice guidelines within an Australian rural hospital; and (ii) to determine the effectiveness of nurse education on that compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 2 publications
2
25
0
4
Order By: Relevance
“…The lack of awareness found in this global survey is consistent with the results of previous country‐specific studies done in Australia, Italy and the US; in these countries, awareness about VTE was low among patients and the general public . However, to our knowledge, ours is the first international study to assess awareness about thrombosis.…”
Section: Discussionsupporting
confidence: 89%
“…The lack of awareness found in this global survey is consistent with the results of previous country‐specific studies done in Australia, Italy and the US; in these countries, awareness about VTE was low among patients and the general public . However, to our knowledge, ours is the first international study to assess awareness about thrombosis.…”
Section: Discussionsupporting
confidence: 89%
“…We believe that continuous education can improve nurses’ knowledge of thromboprophylaxis, as stated. [ 14 ] Moreover, we found that higher levels of training can further improve knowledge. Respondents who had received nationally recognized professional training had the highest correct response rate in our study.…”
Section: Discussionmentioning
confidence: 94%
“…The importance of continuing education has been emphasized by several scholars. [ 7 , 14 ] A previous study demonstrated that only 9% of participants in South Korea received in-service continuous education. [ 15 ] This is relatively, low compared with our results, which may be related to the fact that our respondents were recruited from the best hospitals (AAA-grade) in China.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the Joint Commission emphasis on VTE risk assessment in all hospitalized patients, there remains a gap between current, evidence-based recommendations for VTE prevention and reported nursing practices. (J Vasc Nurs 2014;32: [18][19][20][21][22][23][24] Venous thromboembolism (VTE) manifesting as deep vein thrombosis (DVT) and pulmonary embolism (PE) is a major health care problem affecting hundreds of thousands of Americans annually. Over half of these individuals develop their VTE in hospitals or in the 30 days after hospital discharge.…”
Section: Evaluation Of Hospital Nurses' Perceived Knowledge and Practmentioning
confidence: 99%